Effects of water potential induced by polyethyleneglycol on soybean seed physiological quality - Braccini, Alessandro de Lucca e; Reis, Múcio Silva; Sediyama, Carlos Sigueyuki; Sediyama, Tuneo; Rocha, Valterley Soares (Pesquisa Agropecuaria Brasileira, 1998)
An experiment was carried out in laboratory to evaluate the effects of water potential induced by polyethyleneglycol on soybean seed physiological quality of UFV 10 (Uberaba), IAC 8, Doko RC and Savana cultivars. The seeds were placed to germinate in germitest paper soaked with polyethyleneglycol (PEG 6000) solutions + 0.2% of thiram, using the following osmotic potential levels: 0 (control); -0.05; -0.1; -0.2; -0.4; -0.6 and -0.8 MPa. Seed physiological quality was evaluated by the standard germination test (first count and final count), seedling length and dry matter weight of seedlings. Decreases of the osmotic potential levels caused great reduction in all the characteristics evaluated, which were dependent on the cultivar and on the initial seed physiological quality. Seed vigor was more affected than germination at the same water deficit condition. UFV 10, Doko RC and IAC 8 cultivars, which showed high seed quality, had satisfactory performance until -0.1 MPa osmotic potential level, while Savana, with low seed quality, until -0.05 MPa level. The -0.2 MPa osmotic potential level was the genotype discrimination limit, in relation to length and dry matter weight of seedlings. At -0.6 MPa osmotic potential level, seed germination and vigor were almost null.